SNP Analysis of the SOD1 gene involved in Amyotrophic Lateral Sclerosis (ALS) - Hetal Patel; Anandita Banerjee; Pritha Saha; Subramaniyan Divya; Palaniyandi Ravanan; Priti Talwar (Journal of Taibah University for Science)
ALS is a rare neurodegenerative disease causing the loss of motor neurons in the brain and spinal cord. Mutations in over forty genes, particularly the Superoxide Dismutase 1 (SOD1) gene, are linked to ALS. This study analyses the missense or non-synonymous SNPs (nsSNPs) in the coding region of SOD1 using computational tools to predict the variations in structure and function of protein. The variants with most pathogenicity and clinical significance were further analyzed for stability and found to destabilize the protein structure based on Gibbs Free Energy (ddG) values. These 10 variants were modelled and validated, found occurring mostly in the conserved regions. Among these, 9 nsSNPs reported previously, while 1 novel nsSNP (F46S) was identified, characterized by reduced size and hydrobhobicity in comparison to the wild-type residue. This comprehensive study improves our understanding of the effects of SOD1 SNPs in ALS, thereby aiding in targeted therapies development.